The efficacy of dietary curcumin on growth performance, lipid peroxidation and hepatic transcription factors in rainbow trout Oncorhynchus Mykiss (Walbaum) reared under different stocking densities - Akdemir, Fatih; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Juturu, Vijaya; Şahin, Kazım (Wiley, 2017)
Curcumin, derived from Curcuma longa, exerts antioxidant, antibacterial, anticancer and immunomodulatory properties. This study was conducted to determine the effect of dietary water-soluble curcumin (0, 200 or 400mgkg(-1)) on growth performance and antioxidant status in rainbow trout (Oncorhynchus mykiss, Walbaum) rearing under normal (20kgm(-3)) or high (100kgm(-3)) stocking density conditions. A significant increase in body weight (FBW), feed intake (FI) and weight gain (BWG) was observed in fish fed with curcumin-supplemented diet at 200mgkg(-1) of diet levels of high stocking density conditions (P<0.0001), whereas feed conversion ratio (FCR) was not significant. Also, serum and liver malondialdehyde (MDA) levels were decreased by dietary curcumin in crowded fish (P<0.01, for both). With curcumin supplementation, expressions of heat shock protein 70 (HSP70; P<0.0001) and hepatic nuclear factor kappa-B (NF-B; P<0.01) decreased, whereas expressions of hepatic nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) (P<0.001, for both) increased in fish exposed to high stocking density. In conclusion, curcumin supplementation alleviates adverse effects of high stocking density on performance through modulating expressions of stress-related nuclear transcription factors in rainbow trout.
Keywords: curcumin; performance; lipid peroxidation; transcription factor; stocking density; rainbow trout